UNDERMINES THE THEORETICAL INNOVATION AND AESTHETIC SIGNIFICANCE OF CONTEMPORARY DALIT LITERATURE - Kaur, Japneet; N.K. Gosain, (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to examine social thinker D. R. Nagaraj's speculative technique for dealing with the appraisal of modern Dalit formation. According to Nagaraj, modern Dalit making is a structure made up of deculturedDalits that imparts esteem and capacities in a liberal organisation. He recognises Dalit creative duties in the broader circle of Indian culture and fights for a new style for Indian culture, pardoning instances of a substitute energy for Dalit formation. His goal is to reclaim the Dalit civilizational commitment from Indian tradition. makers, like people and oral social plans. This system undermines the hypothetical progress and exceptional Dalit creating in today's world. BaburaoBagul, a Marathi Dalit academic and essayist, proposes Dalit making as a front line, made, and Ambedkarite custom that reconfigured development, arranged new methods for framing, and envisioned Dalit as a nonexclusive person, lived understanding, and point of view in contemporary Indian creative history. Bagul fights, Dalit making is human and vote-based, since it relies on the humanist traditions of Buddha, Christ, Phule, and Ambedkar, as well as the Western Enlightenment. Following Bagul's chat, an analysis of various Dalit writings graphs Nagaraj's blocksmethodology.